WAKAF TUNAI DAN PEMBERDAYAAN UMAT - Aisa Manilet (TAHKIM, 2013)
In addition to as one of the spiritual-dimensioned teachings aspect, waqf is also a doctrine emphasizing the importance of economic welfare (social dimension), which is expected to play an active role in building and prospering the community. Development of waqf in Indonesia has now increased up to qash waqf (cash). In the historical perspective, waqf was most instrumental in developing social activities, economics and Islamic community culture by establishing the places of worship, education, health, social and public libraries, such as in the middle east. Therefore the existence of waqf in Indonesia either unmoving or moving waqf should be a serious attention from the government, so the usage can impact significantly. Keywords: waqf